Simplify expressions

*To*: mathgroup at smc.vnet.net*Subject*: [mg47856] Simplify expressions*From*: steger at wif.gess.ethz.ch (Thomas Steger)*Date*: Thu, 29 Apr 2004 03:04:58 -0400 (EDT)*Sender*: owner-wri-mathgroup at wolfram.com

Consider the following expression: a+z*k^(b-1)*c^(d-1) Given that y==z*k^b*c^d I would like Mathematica to simplfy the preceding expression to: a+y/(k*c) However, the following command does not work Simplify[a + z*k^(b - 1)*c^(d - 1), y == z*k^b*c^d] Does anyone has a suggestion? Thanks, Thomas